Research on the implementation degree of agile project management methodologies in Russian IT–companies - G. Y. Postnikov; A. G. Dmitriev (Путеводитель предпринимателя)
In the dynamic development context of the information technology sector, especially crucial for Russia at the moment, the adoption of agile project management methodologies becomes a necessary step for companies to effectively respond to changes, enhance product quality, and achieve market success while maintaining competitiveness. Therefore, the aim of this research is to assess the degree of implementation of agile project management methodologies in IT companies in Russia. The study was conducted through online surveys of practicing specialists in the field of managing innovative projects. Specialists were asked a general question about their application of agile methodologies, as well as four questions regarding specific aspects: requirements gathering, planning, communication with clients, and team communication. The article describes which aspects of agile project management methodologies are practiced by surveyed specialists. In conclusion, it is noted that employees tend to use hybrid project management approaches more frequently than pure agile methodologies. Agile principles are more commonly integrated into client communication and team communication, and less so in requirements gathering and planning.